(untitled) (Iranian Journal of Kidney Diseases, 2011)
It is crucial that nephrologists correctly identify acute focal bacterial nephritis, as timely and adequate treatment with appropriate antibiotics can prevent unnecessary investigations, invasive surgical procedures, and renal complications such as renal abscess or renal scar. An urgent kidney ultrasonography should be performed if there is a delayed response to appropriate antibiotic treatment in patients with urinary tract infection. Serial kidney ultrasonography plays a significant role in confirming the diagnosis and monitoring the progression of acute focal bacterial nephritis. We presented a patient with acute focal bacterial nephritis and showed that a serial kidney ultrasonography could prevent the use of invasive investigations and inappropriate surgical procedures.